(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Hydrophilic polymers are widely used to prepare sustained release matrix tablets. These polymers showed their sustained action by forming a barrier of thick gel layer around the matrix. Here swelling of the polymer and erosion of matrix plays a major role to control the release of the drug. In this present study the swelling and erosion properties of some hydrophilic polymers were correlated to their sustaining and rate controlling behavior. Matrix tablets containing hydroxypropyl methylcellulose (HPMC K100cps), carboxymethyl cellulose (CMC 50,000 cps) and methocel K15M CR polymers were prepared. The powder mixture was evaluated for their flow properties and the prepared tablets for their physical parameters. Swelling and erosion index of the tablets were carried out in pH 6.8 phosphate buffer and dissolution in 0.1N HCl (2 hours) followed by pH 6.8 phosphate buffer (8 hours) using USP apparatus II (paddle method) at 50 r.p.m. HPMC K100 cps was found to be not as rate retarding as the other two. From the all results it was observed that F-6 (containing 43.243% methocel K15M CR) showed highest swelling and erosion index (740.589% and 12.017% respectively), slowest release rate (24.491% at 8 hours) and highest MDT value (55.401 hours). Finally it can be concluded that increasing the polymer concentration or polymer’s viscosity grade, swelling and erosion index increases, release rate decreases and MDT value increases. Key words: Aceclofenac; Matrix tablets; HPMC; CMC; Physical parameters; Release kinetics. DOI: 10.3329/bjsir.v45i2.5712 Bangladesh J. Sci. Ind. Res. 45(2), 141-150, 2010